ANALYSIS OF BOOTSTRAPPING DEA EFFICIENCY AND MALMQUIST INDEX IN GOVERNMENT EXPENDITURE ON ISLAMIC HUMAN DEVELOPMENT INDEX IN REGENCIES/CITIES OF EAST JAVA PROVINCE - Mukti, Happy Karunia; Auwalin, Ilmiawan (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
Community welfare is the key to assess the success of an area. The government has a vital role in realizing community welfare. This study aims to evaluate the role of government related to the efficiency of government spending in creating conditions for a prosperous society in the Regency/City in East Java Province in 2011-2015. The efficiency calculation in this study uses the DEA Bootstrapping method with the assumption of Variable Return to Scale (VRS). In contrast, the assessment of the level of community welfare uses the Human Development Index from an Islamic perspective or Islamic Human Development Index (I-HDI). This study also calculated changes in total factor productivity (TFPC) using the Malmquist Index. The data used is sourced from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance of the Ministry of Finance. The results of this study are the performance of regency/city governments in East Java has not yet reached an efficient condition. For the TFPC value, only three regions experienced an increase, one region was in a state of stagnation, while 34 other regions experienced a decrease in the value of TFPC. Keywords: Efficiency of Government Expenditure, Islamic Human Development Index, DEA Bootstrapping and Malmquist Index. REFFERENCE Afifah, F. U. (2017). Pengaruh pengeluaran pemerintah (sektor pendidikan dan kesehatan) dan pengangguran terhadap Islamic Human Development Index (I-HDI) di Indonesia Tahun 2010-2013. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga. Afrial, R. (2009). Kualitas pelayanan publik kecamatan sebuah perubahan kedudukan dan fungsi camat sebagai perangkat daerah. Jurnal Adminstrasi dan Organisasi, 16(2), 87-95. http://journal.ui.ac.id/jbb/article/viewFile/609/594 Assaf. A dan Matawie. (2010). Improving the accuracy of DEA efficiency analysis: a bootstrap application to the health care foodservice industry. Applied Economics, 42(27), 3547-3558. Aydin, N. (2017). Islamic vs conventional Human Development Index: empirical evidence from ten Muslim countries. International Journal of Social Economics, 44(12), 1562-1583. Badan Pusat Statistik. (2015). Indeks Pembangunan Manusia 2014 Metode Baru Chowdhury, H. dan V. Zelenyuk. (2015). Perfomance of hospital services in Ontario: DEA with truncated regression approach. Omega: Canada Coelli, T.J, D.S. Prasada, Christopher, dan G. E. Battese. (2005). An introduction to efficiency and productivity analysis. Springer: Australia. Direktorat Jendral Anggaran. (2016). Efektivitas alokasi anggaran kementerian pariwisata terhadap kunjungan wisatawan mancanegara dan wisatawan nusantara. Espinoza. (2014). Pengaruh Penerapan Anggaran Berbasis Kinerja Terhadap Kinerja Keuangan Pemerintah Kota Medan. Skripsi tidak diterbitkan. Medan: Fakultas Ekonomi Universitas Sumatera Utara. Flokou, A., Aletras, V., & Niakas, D. (2017). A window DEA based efficiency evaluation of the public hospital sector in Greece during the 5 year economic crisis,PLOS ONE, 12(5). https://doi.org/10.1371/journal.pone.0177946 Hasiani, F. (2015). Analisis kualitas sumber daya manusia dan pengaruhnya terhadap pertumbuhan ekonomi di kabupaten Pelalawan. Jom Fekon: Pekanbaru International Labour Organization. (2012). Rencana strategis pariwisata berkelanjutan dan green jobs untuk Indonesia. Kara, M. (2012). Pemikiran Al-Syatibi tentang maslahah dan implementasinya dalam pengembangan ekonomi syariah. ASSETS: Makassar Kholis, N. (2015). Kesejahteraan sosial di Indonesia perspektif ekonomi Islam.Akademika, 20. Kuncoro, A. (2014). https://feb.ugm.ac.id/id/berita/607-peningkatan-kualitas-sumber-daya-manusia-sebagai-pendorong-pertumbuhan-perdagangan. Diakses pada hari rabu, 25 juli 2018 pukul 20.50 wib Mangkoesoebroto, G. (2002). Ekonomi publik. Yogyakarta: BPFE. Mutakin, A. (2017). Teori maqhasid al-syari'ah dan hubungannya dengan metode istinbath hukum. Kanun Jurnal Ilmu Hukum, 19. Odeck, J. (2017). Statistical precision of DEA and malmquist indices: a bootstrap application to Norwegian grain producers. Omega: Norway. Prasetyo, A. D. dan U. Zuhdi. (2013). The government expenditure efficiency towards the human development. Indonesia: Elsevier. Rabbani, M., N. Heidari, H. Farrokhi-Asl. (2016). A bootstrap interval robust data envelopment analysis for estimate efficiency and ranking hospitals. Journal of Industrial Engineering and Management Studies (JIEMS), 3(2). 107-122. Ranis, G dan F. Stewart. (2000). Economic growth and human development. United Kingdom: Pergamon. Rayp G. dan N. V. De Sijpe. (2007). Measuring and explaining government efficiency in developing countries. The Journal of Development Studies, 43(2), 360-381. Renstra Kemenko PMK 2015-2019 Renstra Kesra 2010-2014 Rochmawaty, D. B. (2018). Analisis efisiensi pengeluaran pemerintah terhadap indeks pembangunan manusia kabupaten/kota di Jawa Timur. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisniss Universitas Airlangga. Sulistyaningsih, L. (2018). Evaluasi efisiensi intertemporal dan perubahan total faktor produktivitas industri telekomunikasi asean-5: boostrap window data envelopment analysis dan malmquist index. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisniss Universitas Airlangga. Tsolas, L. F. (2011). Performance assessment of mining operations using nonparametric production analysis: a bootstrapping approach in DEA. Yunani: Elsevier. Tziogkidis, P. (2012). Bootstrap DEA and hypothesis testing. United Kingdom: Econstor. Undang-undang No.11 Tahun 2009 tentang kesejahteraan masyarakat Zangoueinezhad, A dan A. Moshabaki. (2011). Human resource management based on the index of Islamic human development: The Holy Quran's approach.International Journal of Social Economics, 38(12), 962-972.